Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acssuschemeng.5b01055
|View full text |Cite
|
Sign up to set email alerts
|

Acrylate-based Polymerizable Sol–Gel Synthesis of Magnetically Recoverable TiO2 Supported Fe3O4 for Cr(VI) Photoreduction in Aerobic Atmosphere

Abstract: TiO2 synthesized by polymerizable sol–gel approach is used to demonstrate the photoreduction of Cr­(VI) in aqueous medium. Fe3O4 is chosen as the magnetically recoverable support, onto which, 10, 20, 30 and 50% of TiO2 have been dispersed following the polymerizable sol–gel approach. The synthesized materials are characterized using XRD, SEM, XPS, Raman spectroscopy, diffuse reflectance spectroscopy and BET surface area measurement. Different hole-scavengers (oxalic acid, ammonium oxalate and ethanol) and an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…A major peak at 121 cm À1 along with weak peaks at 365, 482, and 603 cm À1 were observed in all cases that can be attributed to the respective vibrational symmetries of E g , B 1g , A 1g , and E g Raman-active modes of anatase TiO 2. 57,65 Due to the presence in minute quantity, the Raman peaks of rutile TiO 2 were not observed in the samples calcined at 600 and 650 C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A major peak at 121 cm À1 along with weak peaks at 365, 482, and 603 cm À1 were observed in all cases that can be attributed to the respective vibrational symmetries of E g , B 1g , A 1g , and E g Raman-active modes of anatase TiO 2. 57,65 Due to the presence in minute quantity, the Raman peaks of rutile TiO 2 were not observed in the samples calcined at 600 and 650 C.…”
Section: Resultsmentioning
confidence: 98%
“…The PSG approach has been shown to be suitable for high-throughput step-and-ash imprint lithography for various oxides 55 and to synthesize supported oxide photo-catalysts. 56,57 Despite the high potential, the PSG approach based on free radical polymerization of methacrylates is vulnerable to radical scavenging by oxygen that could affect the degree of polymerization, which in turn could effect on the quality of imprinting. This warrants purging/bubbling of inert gas into the metal-containing resin before patterning in order to eliminate any dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the composite photocatalysts exhibited a higher rate of photoreduction of Cr(VI) as compared to the nonsupported bulk TiO 2 as well as calcined Fe 3 O 4 . In fact, 30% TiO 2 /Fe 3 O 4 has shown the highest Cr(VI) photoreduction rate due to formation of effective heterojunction by the loading of 30% TiO 2 over Fe 3 O 4 [158]. …”
Section: Reviewmentioning
confidence: 99%
“…The percentage removal of Cr(VI) was found to be 93%, 88%, and 80% for the first, second and third cycles, respectively, for TiO 2 /CdS films, indicating its high photostability [200]. Challagulla et al reported that TiO 2 /Fe 3 O 4 composite photocatalysts retained their efficiency towards reduction of Cr(VI) after the fourth cycle [158]. About 84% of it was recovered at the end of the fourth cycle.…”
Section: Reviewmentioning
confidence: 99%
“…On the other hand, Cr(VI) is a highly hazardous species and possesses acute toxicity as a carcinogen. Conversion of Cr(VI) to Cr(III) is considered to be a green process, as the latter is an essential metabolite for the insulin function . Figure (a) shows the photocatalytic degradation of methylene blue under UV light with 500, 700 and 900 °C calcined SrTiO 3 and the ball milled samples.…”
Section: Resultsmentioning
confidence: 99%